Escalonamento na produção de mudas de marmeleiro: armazenamento a frio de materiais propagativos, uso de acido indolbutirico e métodos de enxertia - Celant, Viviane Marcela (2010)
Developed a protocol for the production of seedlings grafted on quince rootstock 'Japanese' (Chaenomeles sinensis) in winter. Thus, the present work had for objective to study the cold storage of cuttings of quince cultivars and treatment with indolbutyric acid, the viability of the budsticks storage of different cultivars of quince by cold storage, and to verify the grafting method to promote better development of the graft and also to study the viability of conservation and cryopreservation of seeds of quince Japones . To achieve this goal, three experiments had been carried through. In the firs experiment, were used hardwood cuttings of quince 'Cheldow' and 'Marmelo Pera'. Some of the cuttings were stored in cold, and other part was placed directly to take root, in the rooting bed in the nursery. The cuttings were treated with different concentrations of indolbutyric acid: 0, 1000, 2000 and 3000 mg L-1, for 10 seconds. After 75 days, we evaluated the percentage of rooted cuttings, callous, sprouting and alive, average number of leaves and shoots, length of shoots and roots, mass dries average of the aerial part and roots. In the second experiment branches of quince Japones (Chaenomeles sinensis), Smyrna , Portugal , Mendoza Inta-37 and Provence (Cydonia oblonga) had been collected in July of 2008. A part of the branches were used for grafting by the methods of budding and cleft grafting in seedlings of nine months of age of the rootstock 'Japanese' and another part was stored in cold chamber at 4 ° C for 30 and60 days. After 60 days of grafting, was measured the percentage of sprouted of the rootstock and the final 120 days of the completion of grafting the length, diameter and average dry weights of the grafts. In the third experiment, a part of the seeds of quince 'Japanese' were sown immediately (32.8% moisture) and the remain had the humidity lowered for 14,14%. Part of the seeds with 14,14% humidity was stratified for 20 days in refrigerator in Petri dishes lined with moistened cotton, another part was stored for 3, 6, 9 and 12 months within plastic tubes in the temperature of 20 ° C 5 o C and -12 o C, and the other part of the seeds were placed in cryotubes and stored in cryogenic storage for 20 days. After storage, all seeds were stratified and sown in the same way and placed in chamber B.O.D. We evaluated the germination percentage at the end of stratification and four assessments spaced seven days. It was concluded that the cuttings of cultivating `Cheldow' if propagate more easily, cold storage increases the percentage of rooting and sprouting, with higher rooting when treated with 2000 mg L-1 IBA; to cultivate although them to present difference, it is recommended that the branches are stored for up to 30 days if using the grafting method of grafting. You can store the seeds of quince for up to 9 months under room temperature (20 C) or for long periods through cryopreservation, allowing the assignment of the production of rootstocks and still supporting the storage of germplasm